Training on Identifying Buyer Behavior in the Business Market for SMEs - Rasyid, Ardiansyah; Aurellia, Claudya; Anastasya, Meilani; Natalie, Michelle; Marcella, Sherlyn (International Journal of Social Science and Community Service, 2024)
In today's era, business actors purchase goods and services for use in the production of their products and services with varying behaviors. In the business market, there are various buyer behaviors that require more consideration in making purchasing decisions. There are four factors that can influence purchasing decisions in the business market. The partner in this activity operates a mochi snack business located in Kemayoran, Central Jakarta. In its operations, the partner faces challenges, particularly in identifying buyer behavior in the business market. The training activity for the partner was conducted online via Zoom. The purpose of this activity is to assist the partner in enhancing their knowledge of identifying buyer behavior in the business market. The method used in this activity involves training on identifying buyer behavior in the business market, focusing on how the partner interacts with their surroundings, so that the problems faced by the partner can be addressed through the training and solutions provided. The outcomes of the activity include publications in journals and intellectual property rights (HKI).